2009
DOI: 10.1038/sj.bjc.6605374
|View full text |Cite
|
Sign up to set email alerts
|

A randomised phase II study of modified FOLFIRI.3 vs modified FOLFOX as second-line therapy in patients with gemcitabine-refractory advanced pancreatic cancer

Abstract: BACKGROUND: Only a few clinical trials have been conducted in patients with advanced pancreatic cancer after failure of first-line gemcitabine-based chemotherapy. Therefore, there is no current consensus on the treatment of these patients. We conducted a randomised phase II study of the modified FOLFIRI.3 (mFOLFIRI.3; a regimen combining 5-fluorouracil (5-FU), folinic acid, and irinotecan) and modified FOLFOX (mFOLFOX; a regimen combining folinic acid, 5-FU, and oxaliplatin) regimens as second-line treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 24 publications
6
93
0
1
Order By: Relevance
“…Nevertheless, antagonism with AdDD was not observed in any cell line, suggesting that the deletion of E1B19K might push the balance towards cell death. The degree of sensitization with the combination of AdDD and irinotecan, a topoisomerase I inhibitor, 34,44 was similar to that obtained in combination with gemcitabine in SUIT-2, PT45 and MIA PaCa-2 cells, with two-to fourfold reductions in EC 50 values. In contrast to gemcitabine, the enhancement of cell killing was independent of the sensitivity of each cell line to drug and might reflect the different mechanisms of action for these drugs.…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, antagonism with AdDD was not observed in any cell line, suggesting that the deletion of E1B19K might push the balance towards cell death. The degree of sensitization with the combination of AdDD and irinotecan, a topoisomerase I inhibitor, 34,44 was similar to that obtained in combination with gemcitabine in SUIT-2, PT45 and MIA PaCa-2 cells, with two-to fourfold reductions in EC 50 values. In contrast to gemcitabine, the enhancement of cell killing was independent of the sensitivity of each cell line to drug and might reflect the different mechanisms of action for these drugs.…”
Section: Discussionsupporting
confidence: 60%
“…[2][3][4] Combining gemcitabine with 5-FU improved survival in certain patients, 5 whereas combinations with other cytotoxic drugs resulted in negligible survival benefits. [6][7][8] Improved therapies with greater efficacy and different mechanisms of action are therefore needed.…”
Section: Introductionmentioning
confidence: 99%
“…FOLFIRINOX is a standard first line regimen for mPC and the respective contributions of the individual therapeutic components (5FU, oxaliplatin, irinotecan) and tumor biomarkers (TOPO1, TS) to the efficacy of the regimen are not known. A number of pilot studies in mPC have suggested that FOLFIRI is active (23,24) and support for this hypothesis also comes from a recently completed study (NAPOLI-1), which established MM398 in combination with 5-FU as an effective 2nd line regimen (13). The therapeutic ratio of this combination could be enhanced if activity is increased in tumors with TOPO1 expression.…”
Section: Discussionmentioning
confidence: 96%